TECHNICAL EFFICIENCY ANALYSIS OF SUGAR CANE PRODUCTION IN SUTOJAYAN VILLAGE, PAKISAJI SUB-DISTRICT, MALANG, EAST-JAVA, INDONESIA - Nanda Anggiadita; Sujarwo Sujarwo (Socio-Economics/Agribusiness Department, 2016)
Government has a sugar self-sufficiency program in 2020 up to 2025. However, based on data from the Directorate General of Plantation (2013), the amount of sugar production is lower than the national sugar demand. The research location is Sutojayan village, Pakisaji district, Malang Regency, East Java, Indonesia. The purposes of this research are: (1) analyzing the factors that affect sugar cane production, (2) analyzing the level of technical efficiency on the sugar cane production, and (3) identifying the characteristics of respondents related to the level of efficiency achieved in the sugar cane production activities. The methods used in this research are SFA (Stochastic Frontier Analysis) approach and descriptive statistical analysis. Based on the results, seed and labor affect the increase of sugar cane production significantly. Farmers at the research location also has 5 percent opportunity to increase the production of sugar cane. The farmer respondents have high technical efficiency which is 95%. The characteristics of respondents generally consist of the age between 51 – 60 years, the last level of education is primary school, sugar cane farmer is the main job, the household size is 3 – 4 people, the experience of sugar cane farmer ranged between 21 – 30 years, using the BL (Bululawang) variety, the farm size of sugar cane is 0.10 – 0.50 hectares, and the status of land is the owner.